Advantages of using paleontological components in extracurricular activities in the english language for middle -school students - Kalizhanova, A.N.; Makarovskaya, P.Y.; Aupenova, A.U.; Shelestova, T.Y.; Maryshkina, T.V.; Ishmuratova, M.Y. (Revista Entrelinguas, 2021)
The article explores the use of the elements of paleontology in extracurricular activities in the English language, since the materials, enriched with the linguocultural and historical components, contribute to the introduction of students to the linguistic cultures of other ethnic groups within a single state and increase the motivation for learning languages. The correct use of such materials in the project activities of schoolchildren provides opportunities for developing social activism and improving cross-cultural and linguistic competencies. The elements of paleontology in extracurricular activities in the English language could also contribute positively to the expansion of knowledge base in school subjects, such as English and Biology, and could potentially provide a deeper immersion in the culture and history of their country and their small homeland.
Keywords: Dinosaurs; Elements of paleontology; Extracurricular activities in the English language; Paleontological finds; Social activism